Analisis Emisi Gas Rumah Kaca (CO dan N2O) di Pelabuhan Penyeberangan Torobulu Konawe Selatan: Studi Kasus : Akibat Arus Mudik Lebaran Tahun 2017-2021 - Pranata, Anal; Sumarlin, Sumarlin; Srikandi, Eka Dian (Jurnal TELUK: Teknik Lingkungan UM Kendari, 2022)
The results showed that the number of vehicles that passed in the South Konawe Torobulu ferry port area was 9686 vehicles during the eid homecoming flow based on 2017 and the minimum number of vehicles that crossed as many as 3596 vehicles during Eid homecoming in 2020, for the total load of CO emissions generated according to the type of vehicle the most The amount produced is 93,010,624 (g/month/km) for 2020 and for the total load of N2O emissions produced which are differentiated according to the type of vehicle, the largest produced is 40,695,872 (g/month/km) 2017 date. The CO load produced is according to the type of vehicle, the largest produced is 0.09 (tons/month) in 2021 date and for the N2O emission load is produced according to the type of vehicle, the largest is 0.0601 (tons/month) 2018 date. The results of the analysis using Quantum GIS that the Green Open Space at the South Konawe Torobulu ferry port with an area of 52 .299 m2 of which there is tree cover vegetation with an area of 11,394 m2 and ornamental plant vegetation with an area of 2810 m2, with the ability to absorb 151,560208 kg/hour, for this reason it is necessary to add 1.65 hectares to be able to absorb Green Open Space, so that vehicle CO2 emissions due to The resulting Eid homecoming flow can be absorbed more optimally.